2020
DOI: 10.1007/s10734-020-00570-x
|View full text |Cite
|
Sign up to set email alerts
|

What actually works to enhance graduate employability? The relative value of curricular, co-curricular, and extra-curricular learning and paid work

Abstract: The focus on short-term graduate employment metrics has catalysed the employability agenda as a strategic directive in universities. A raft of embedded, co-curricular and extra-curricular activities have emerged for developing employability. Their relative value lacks empirical exploration. This study explored graduates' selfreported participation in, and their perspectives on the value of, a range of embedded, extra-curricular and cocurricular learning activities, as well as paid work, for employability. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 46 publications
(45 reference statements)
7
103
1
6
Order By: Relevance
“…We agree with Bridgstock (2019), who stated that other platforms such as LinkedIn might also help developing professional identity, although the latter study was not based on long-term observation of professionals. We also believe that there is a teachable knowledge that can enhance students' identity development through SNSs as claimed by previous studies (Jackson & Bridgstock, 2020;Jawed et al, 2019;Starcic et al, 2017). Floridi (2014) already noticed: the study clearly demonstrated that SNS activities became part of the users' info-space and that their information became part of them and part of their identity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We agree with Bridgstock (2019), who stated that other platforms such as LinkedIn might also help developing professional identity, although the latter study was not based on long-term observation of professionals. We also believe that there is a teachable knowledge that can enhance students' identity development through SNSs as claimed by previous studies (Jackson & Bridgstock, 2020;Jawed et al, 2019;Starcic et al, 2017). Floridi (2014) already noticed: the study clearly demonstrated that SNS activities became part of the users' info-space and that their information became part of them and part of their identity.…”
Section: Discussionsupporting
confidence: 70%
“…These studies lack a developmental depth, though. Previous studies suggest providing institutional guidance for students regarding the use of social networking sites and forming their digital professional identity in SNSs (Jackson & Bridgstock, 2020;Jawed et al, 2019;Starcic et al, 2017). There is a lack of studies tracing the actual role of SNSs affordances in professional identity development: How do adults, in their lifelong professional development, use SNSs?…”
Section: Professional Identity Development and Snssmentioning
confidence: 99%
“…Such a student is competent enough to complete task(s) with perfection and confidence. The same person is capable to marketing the organization before many stakeholders for better collaboration (Jackson & Bridgstock, 2020).…”
Section: Indonesian Journal On Learning and Advanced Educationmentioning
confidence: 99%
“…We contend that a pedagogy for employability is a pedagogy of metacognition in which learners actively engage in the exploration of explicit learning goals and in dialogue about learning processes and learners' cognitive styles (Cullen & Harris, 2009;Evans, 2018). This suggests a critical, responsive pedagogy in which the theoretical underpinnings of learning and teaching, and its application in future life and work, are explicitly articulated and supportive of the learning purpose (Evans, Muijs, & Tomlinson, 2015;Jackson & Bridgstock, 2020). A pedagogy for employability, then, should explicitly develop learners' disciplinary and broader metacognitive understanding not as an outcome of higher education but as an integral component of student engagement and retention (see Evans & Kozhevnikov, 2013;Kift, 2019).…”
Section: A Pedagogy For Employabilitymentioning
confidence: 99%